Cutting force prediction in orthogonal turn-milling by directly using engagement boundaries. Issue 1 (September 2016) - Qiu, Wenwang; Liu, Qiang; Ding, Ji; Yuan, Songmei
Abstract Despite of the studies in the last decades, there are still some gaps in understanding of the distinctive behaviors of orthogonal turn-milling. In order to improve the performance of this new technology, deeper investigations are required. This work deals with the mechanics in non-eccentric orthogonal turn-milling. The engaged areas of both side edge and end edge are analyzed. Then, the boundary conditions used to extract them are derived. The two sets of cutting force coefficients for the side edge and end edge are calibrated based on slot milling and plunge milling, respectively. The total cutting forces are calculated as a sum of the cutting forces on both side edge and end edge. The proposed cutting force model is validated experimentally on a five-axis machine tool. In addition, comparative experiments have been conducted to investigate the effects of cutting depth and longitudinal feed rate on the cutting force in tool axis direction.